THE INFLUENCE OF ORGANIZATIONAL CULTURE AND JOB SATISFACTION ON ORGANIZATIONAL CITIZENSHIP BEHAVIOR (OCB) IN EMPLOYEES OF CV SUMBER CAHAYA MOTOR PALEMBANG - Silvi Riyanti Agustin; Muhamad Helmi; Destia Aktarina; Nurul Mardiyyah Pratiwi (Program Studi Manajemen Fakultas Ekonomi Universitas Palembang, 2024)
Abstract: strong features of CV Sumber Cahaya Motor's corporate culture can be seen in the behavioral dimensions of courtesy and altruism, where employees are very conscious of the importance of fostering strong connections and supporting one another. Nonetheless, there are shortcomings in the areas of conscientiousness and sportsmanship, as workers frequently show a lack of initiative when working beyond their assigned duties and a lack of enthusiasm when confronted with directives or extra work that is not related to their primary duties. Obviously, this contributes to workers' dissatisfaction with their jobs. This study aimed to characterize organizational culture, job satisfaction, and organizational citizenship behavior (OCB) in part-time and full-time CV Sumber Cahaya Motor Palembang personnel. Saturated sampling methodology was employed in this investigation, with a total of 40 employees as the sample. This study employed a quantitative methodology. This study used a descriptive and verification analytical methodology. The study's findings suggest that work satisfaction and company culture have a big impact on how employees behave in terms of organizational citizenship. With a combined 52.8% contribution to OCB, both variables have a significant impact. To support the rise in employee OCB, management must continue to fortify organizational culture and raise job satisfaction.